Hormonal profiles and metabolic changes in women diagnosed with concomitant Hashimoto’s thyroiditis and polycystic ovary syndrome via sonography - Ahmed, Abeer Wali; Abdul-QaderKhuder, Hana; Jasim, Shaymaa A.H.; Mohsein, Osama A. (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. Women with both Hashimoto’s thyroiditis (HT) and polycystic ovary syndrome (PCOS) often experience hormonal imbalances and metabolic changes. We investigated the correlation between sonographic changes and hormonal abnormalities in women with Hashimoto’s thyroiditis and PCOS. Material and methods. A case-control study including 150 women with PCOS and Hashimoto’s thyroiditis, and 50 healthy women as a control group, was conducted at Al-Habobbi Teaching Hospital from 7/1/2023 to 7/10/2024. Lipid, blood sugar, luteinizing hormone (LH), follicle-stimulating hormone (FSH), prolactin, testosterone, and thyroid hormones were assessed, the groups had similar mean ages and smoking rates. Results. When the case group was compared with the control group, significant hormonal and metabolic differences were observed. Specifically, levels of LH were significantly higher in the case group (14.68±1.21 vs. 3.31±1.03 mIU/mL, p=0.001), as were levels of FSH (14.85±1.07 vs. 5.26±0.51 mIU/mL, p<0.001), prolactin (28.90±1.34 vs. 7.02±1.16 ng/dL, p<0.001), and testosterone (57.71±2.61 vs. 12.41±2.27 ng/dL, p<0.001). In terms of lipid profile, the case group showed elevated total cholesterol (229.93±14.61 vs. 134.51±9.38 mg/dL, p<0.001), triglycerides (287.78±41.43 vs. 128.04±10.20 mg/dL, p<0.001), low-density lipoprotein (LDL) (136.98±20.02 vs. 58.67±11.45 mg/dL, p<0.001), and very low-density lipoprotein (VLDL) (57.55±8.28 vs. 25.60±2.04 mg/dL, p<0.001), while levels of high-density lipoprotein (HDL) were significantly lower (35.39±3.54 vs. 50.23±4.55 mg/dL, p<0.001). Regarding thyroid function, thyroxine (T4) levels were significantly reduced in the case group (9.80±0.77 vs. 15.02±1.25, p<0.001), while thyroid-stimulating hormone levels were elevated (6.25±1.10 vs. 2.17±0.74 μIU/mL, p<0.001). Conclusion. These findings suggest a potential complex interaction between the thyroid and reproductive glands, which may influence the pathogenesis and metabolic effects of these endocrine disorders. However, the individual and combined effects require further detailed investigation.